Genome-Wide Association Study of Liver Enzymes in Korean Children - Tae-Joon Park; Joo-Yeon Hwang; Min Jin Go; Hye-Ja Lee; Han Byul Jang; Youngshim Choi; Jae Heon Kang; Kyung Hee Park; Min-Gyu Choi; Jihyun Song; Bong-Jo Kim; Jong-Young Lee (Genomics & Informatics)
Liver enzyme elevations, as an indicator of liver function, are widely associated with metabolic diseases. Genome-wide population-based association studies have identified a genetic susceptibility to liver enzyme elevations and their related traits; however, the genetic architecture in childhood remains largely unknown. We performed a genome-wide association study to identify new genetic loci for liver enzyme levels in a Korean childhood cohort (n = 484). We observed three novel loci (rs4949718, rs80311637, and rs596406) that were multiply associated with elevated levels of alanine transaminase and aspartate transaminase. Although there are some limitations, including genetic power, additional replication and functional characterization will support the clarity on the genetic contribution that the ST6GALNAC3, ADAMTS9, and CELF2 genes have in childhood liver function.